(untitled) - Wheeler, Lisa; 1963-; Siegel, Mark (New York, 2004)
A motley crew of dogs presents a rhyming tale of seagoing adventure, illustrated as if it were a stage play.
"A Richard Jackson Book."
Keywords: Stories in rhyme; Sea stories; Fiction; Fiction; Dogs; Seafaring life